2017
DOI: 10.3389/fphys.2017.00159
|View full text |Cite
|
Sign up to set email alerts
|

Bosutinib Therapy Ameliorates Lung Inflammation and Fibrosis in Experimental Silicosis

Abstract: Silicosis is an occupational lung disease for which no effective therapy exists. We hypothesized that bosutinib, a tyrosine kinase inhibitor, might ameliorate inflammatory responses, attenuate pulmonary fibrosis, and thus improve lung function in experimental silicosis. For this purpose, we investigated the potential efficacy of bosutinib in the treatment of experimental silicosis induced in C57BL/6 mice by intratracheal administration of silica particles. After 15 days, once disease was established, animals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 76 publications
7
28
0
Order By: Relevance
“…Therefore, BMS-345541 and DMSO were considered safe and non-toxic. This finding was similar to the results of previous studies ( 15 , 38 ).…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, BMS-345541 and DMSO were considered safe and non-toxic. This finding was similar to the results of previous studies ( 15 , 38 ).…”
Section: Discussionsupporting
confidence: 93%
“…The same group demonstrated that shifting to a type‐1 macrophage activation by administration of IL‐12 resulted in NO synthase‐2 (NOS2, iNOS) overexpression and reduction of fibrosis intensity . Moreover, other studies also reported that the modification of M1/M2 balance is critical in the development of particles exposure caused pulmonary disease . Our study only showed that VD treatment could protect against particles‐induced lung injury by decreasing the macrophages' apoptosis and DNA damage, but not investigated the polarization of macrophage with particle exposure.…”
Section: Discussionmentioning
confidence: 57%
“…The main function of MMP2 and MMP9 is to degrade and restore the extracellular matrix and maintain the dynamic balance in basement membrane. MMP2 and MMP9 can destroy the basement membrane and promote inflammation, play an important role in reconstruction extracellular matrix in the process of tissues injury 34 . In this study, ICAM-1, MMP2, MMP9 significantly increased and ZO-1 significantly reduced in lung I/R rat animals, pretreatment with CVF can change the expressions of ICAM-1, ZO-1, MMP2, MMP9.…”
Section: Discussionmentioning
confidence: 99%